IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA BANJIR DI KECAMATAN SIDOMULYO OLEH PEMERINTAH KABUPATEN LAMPUNG SELATAN - Hinfa Mosshananza (DEMOKRASI, 2022)
Indonesia is one of the countries that experiences floods almost every season. At the beginning of the year, precisely in January 2020, rainfall in several areas in South Lampung Regency increased, one of which was in Sidomulyo District, South Lampung Regency. The role of the South Lampung Regency Government, which in this case is carried out by the Regional Disaster Management Agency (BPBD) when disaster management is very responsive and crucial. This study aims to determine the implementation of flood disaster management policies by the South Lampung Regency Government and the factors that hinder flood management. This research method uses a qualitative descriptive approach. The results of research in the implementation of flood disaster management policies by the South Lampung Regency Government in Sidomulyo District based on aspects of communication, disposition and organizational structure have been carried out properly, while based on resource aspects have not been carried out properly. The factors that hinder flood management such as poor communication network facilities, lack of funding aspects, slow handling of health services and evacuations and lack of quality and quantity of Human Resources (HR) in supporting disaster management. Keywords: Implementation, Policy, Flood DisasterIMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA BANJIR DI KECAMATAN SIDOMULYO OLEH PEMERINTAH KABUPATEN LAMPUNG SELATAN